Silicate solubilizing bacteria for improved growth of rubber and suppression of white root rot fungal pathogen Rigidoporus microporus - Othman, Radziah; Shabbir, Imran; Sulaiman, Zulkefly; Abd Samad, Mohd Yusoff; Wong, Mui Yun; Md Jaafar @ Ahmad Jaafar, Noraini (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Silicate solubilizing bacteria (SSB) play an important role in solubilizing insoluble forms of silicates in soil. The uptake of soluble silicon can help plant to be more resistant against fungal pathogens. Bacterial strains isolated from rubber plantation were screened for solubilization of silicate. Only five bacterial isolates were capable of solubilizing silicate. These isolates were further tested for growth promotion and antagonistic activity against Rigidoporus microporus. The highest silicate (solubilizing index 4.67±0.65) was observed for SSB7 isolate. In liquid assay for silicate solubilization the highest solubilization (11.55±0.58 mg L-1) was observed for SSB7 isolate compared to the other isolates at 10 days of growth. The dual culture antagonistic assay showed that all five SSB isolates strongly inhibited the growth of R. microporus. The highest inhibition (PIRG 57.24%) was recorded for SSB7 followed by SSB10 (PIRG 45.12%). These isolates were also able solubilize phosphate, potassium, produce indole-3-acetic acid (IAA), with the highest IAA production (19.96±1.79 μg mL-1) found by SSB7 isolate. All SSB isolates were able to produce siderophore. Isolates SSB7 and SSB10 were able to secrete cellulase while only SSB7 had the ability to produce pectinase. These bacterial isolates showed the ability to improve growth of rubber seedlings and inhibit the development of white root rot disease.